(untitled) (Sciences & Technology. A, exactes sciences, 2011)
In this paper, we study a mixed problem for a third order parabolic equation with non classical boundary condition. We prove the existence and uniqueness of the solution. The proof of the uniqueness is based on a priori estimate and the existence is established by Fourier’s method.